OPTIMIZATION OF DELIVERY COSTS USING VOGEL'S APPROXIMATION METHOD (VAM) AND STEPPING STONE METHODE - Siti Handayani; Rina Filia Sari; Rima Aprilia (Journal of Mathematics and Scientific Computing With Applications, 2021)
Distribution is the delivery of goods from source to destination. Transportinggoods from source to destination requires transportation and distribution costs.Distributing goods requires cost optimization. This research optimizes costsusing a transportation model. Optimization is an activity to get the best resultunder a given situation. The ultimate goal of these activities is to minimize effortor maximize results. The transportation model is a model used to regulate thedistribution of sources that provide the same product to destinations that needit optimally. The transportation model can be completed in two stages, namelythe initial solution using the Vogel's Aproximation Method (VAM) and theoptimum solution using the Stepping Stone method. This study aims tooptimize the cost of distribution of goods from source to destination at UDYosarita. The results of the study using the Vogel's Aproximation Method(VAM) as the initial solution and the Stepping Stone method as the optimumsolution in April 2019 were Rp.4,615,000, in May 2019 Rp.4,810,000, in June2019 Rp. 4,910,000.